A Novel Method for Metal-Activated Carbon Particle Production and Adsorption Effects of Harmful Gas - Oh, Won-Chun; Kim, Jong-Gyu; Kim, Hyuk; Zhu, Lei; Park, Chong-Yeon; Choi, Jong-Geun; Ghosh, Trisha; Meng, Ze-Da (Asian Journal of Chemistry, 2012)
The aim of this study is to investigate the effect of different metal treated carbon for adsorption harmful gas. In this study we used a novel method to mass production metal treated carbon. And the control of the concentration of metal during the produce process by using control the number of nozzle. The samples were characterization by EDX and XRD. The adsorption effect of harmful gas was checked by use of different samples.